Spotted cucumber beetle Diabrotica undecimpunctata howardi Barber (Insecta: Coleoptera: Chrysomelidae) - Harsimran Kaur Gill; Gaurav Goyal; Jennifer Gillett-Kaufman (EDIS, 2013)
Spotted cucumber beetle is a major agricultural pest of North America. Another name for the spotted cucumber beetle is “southern corn rootworm”. Many Diabrotica species cause damage to field crops, especially corn, making these beetles a major agricultural concern. Because of the subterranean nature of their larvae, these insects are hard and expensive to control. This 6-page fact sheet was written by Harsimran Kaur Gill, Gaurav Goyal, and Jennifer Gillett-Kaufman, and published by the UF Department of Entomology and Nematology, September 2013.